Free Trade and Globalisation: Boon or Bane for the Emerging World? - Ron, Matthews (2016)
Globalisation, growth and equality are not always compatible. Income disparity amongst the peoples of the emerging world has become an issue of increasing concern, especially in the wake of the current global economic crisis.